Pengaruh literasi keuangan dan gaya hidup terhadap pengelolaan keuangan mahasiswa akuntansi di Sukabumi - Nasriah, Sri (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This study was conducted to determine the effect of financial literacy and lifestyle on the financial management of Accounting student in Sukabumi. This study is a quantitative study with data collection techniques using a questionnaire. The sample used in this study amounted to 130 accounting students in Sukabumi. This study uses simple random sampling method. The data analysis technique uses multiple linear analysis andis processed using SPSS 24. The result of this study are financial literacy variables affect the financial management of accounting students in Sukabumi, as well as lifestyle variables affect the financial management of accounting students in Sukabumi.